Mother Spain: A Reading of María Zambrano’s Aesthetic Thinking - Soto, Pamela; Espinoza Lolas, Ricardo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
This article presents María Zambrano’s aesthetic thinking based on her critique of modern reason. The itinerary of this reading follows the chronological horizon of the philosophy in Chile between the end of 1936 and the beginning of 1937, as well as her intellectual work during this phase of her life. This reading itinerary is presented in three sections: the first describes Zambrano’s cultural work in Chile; the second analyzes poetic reason based on the texts she published in Chile, which refer to the improvement of the understanding as a critique of the discourse of modernity; and the third contributes to identifying some of the characteristics that define the aesthetic thinking of philosophy.